Support for Young Black Urban Women After Perinatal Loss. Issue 1 (January 2019) - Fenstermacher, Kimberly H.; Hupcey, Judith E.
Abstract: Purpose: To describe the bereavement support needs of black urban women in late adolescence after perinatal loss. Study Design and Methods: Eight black women aged 18 to 21 years who had experienced recent perinatal loss were interviewed in person or by telephone at three points in the 12 weeks that followed their loss to describe their perinatal bereavement experience and support needs. Data from the interviews were analyzed using constant comparative analysis. Results: Black adolescent women need culturally appropriate bereavement support targeted at key transition points along the bereavement trajectory. They need accurate information, compassionate and respectful communication, and support from their mothers, grandmothers, and other women from their community of faith who have experienced perinatal loss. They value mementos, such as photographs and footprints. Clinical Implications: Nurses are well-positioned to be consistent caregivers and to provide clear, compassionate communication and anticipatory guidance to young black women experiencing perinatal loss. Attending to spiritual needs, harnessing family support, providing mementos, and encouraging reflection through journaling may help adolescent women find meaning and new perspectives on their bereavement experience. Abstract : Young black women shared their experiences with perinatal loss at three points during the 12 weeks after their loss. There are opportunities at several points of transition in the perinatal bereavement trajectory when nurses can offer culturally sensitive bereavement support. Suggestions for nursing care during each time frame are presented based on study findings.